2019
DOI: 10.1002/jum.15155
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Anti–Prostate‐Specific Membrane Antigen Single‐Chain Variable Fragment–Loaded Nanobubbles as a Novel Targeted Ultrasound Contrast Agent for the Diagnosis of Prostate Cancer

Abstract: Objectives To prepare optimized prostate‐specific membrane antigen (PSMA) single‐chain variable fragment (scFv)–loaded nanobubbles (NBs) as a novel targeted ultrasound (US) contrast agent for diagnosis and treatment of prostate cancer (PCa). Methods Prostate‐specific membrane antigen scFv‐loaded NBs were prepared by membrane hydration and biotin‐streptavidin conjugation. Flow cytometry was used to observe the binding rate of the targeted NBs to PSMA‐expressing cells. Contrast‐enhanced US was used to monitor ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For instance, two independent studies have reported prostate specific membrane antigen (PSMA, overexpressed in prostate cancer)-targeted-NBs as a novel ultrasound contrast agent for the diagnosis of prostate cancer. 241,242 As another example, Yu et al developed targeted NBs by coupling anti-G250 nanobodies to lipid-shell NBs to target renal cell carcinoma cells for ultrasound molecular imaging and diagnosis of renal tumors. 243 breast cancer cells.…”
Section: Molecular Imagingmentioning
confidence: 99%
“…For instance, two independent studies have reported prostate specific membrane antigen (PSMA, overexpressed in prostate cancer)-targeted-NBs as a novel ultrasound contrast agent for the diagnosis of prostate cancer. 241,242 As another example, Yu et al developed targeted NBs by coupling anti-G250 nanobodies to lipid-shell NBs to target renal cell carcinoma cells for ultrasound molecular imaging and diagnosis of renal tumors. 243 breast cancer cells.…”
Section: Molecular Imagingmentioning
confidence: 99%
“…This feature makes it one of the most important biomarkers in the diagnosis and treatment of PCa. Therefore, some studies focused on the construction of targeted nanobubbles (NBs) with a diameter of less than 700 nm to achieve specific ultrasound-enhanced imaging of prostate cancer cells (102)(103)(104). At present, PSMAtargeting, indocyanine green (ICG)-loaded nanobubbles (NBs) (102) and PSMA single-chain variable fragment (scFv)-loaded NBs have been reported (104).…”
Section: Contrast−enhanced Ultrasoundmentioning
confidence: 99%
“…Therefore, some studies focused on the construction of targeted nanobubbles (NBs) with a diameter of less than 700 nm to achieve specific ultrasound-enhanced imaging of prostate cancer cells (102)(103)(104). At present, PSMAtargeting, indocyanine green (ICG)-loaded nanobubbles (NBs) (102) and PSMA single-chain variable fragment (scFv)-loaded NBs have been reported (104). These new targeted NBs have been proven to be excellent US contrast agents that extend the signal enhancement time and have stronger penetrating ability and higher specificity (105,106).…”
Section: Contrast−enhanced Ultrasoundmentioning
confidence: 99%